Kinase activity profiling reveals active signal transduction pathways in pediatric acute lymphoblastic leukemia: A new approach for target discovery. Issue 7 (21st January 2015) - van der Sligte, Naomi E.; Scherpen, Frank J. G.; Meeuwsen–de Boer, Tiny G. J.; Lourens, Harm Jan; ter Elst, Arja; Diks, Sander H.; Guryev, Victor; Peppelenbosch, Maikel P.; van Leeuwen, Frank N.; de Bont, Eveline S. J. M.
<x xml:space="preserve">Abstract</x> Still about 20% of patients with acute lymphoblastic leukemia (ALL) struggle with relapse, despite intensive chemotherapy. We and others have shown that kinase activity profiling is able to give more insights in active signal transduction pathways and point out interesting signaling hubs as well as new potential druggable targets. With this technique the gap between newly designed drugs and ALL may be bridged. The aim of this study was to perform kinome profiling on 20 pediatric ALL samples (14 BCP‐ALL and six T‐ALL) to identify signaling proteins relevant to ALL. We defined 250 peptides commonly activated in both BCP‐ALL and T‐ALL representing major signal transduction pathways including MAPK, PI3K/Akt, and regulators of the cell cycle/p53 pathway. For 27 peptides, differentially phosphorylation between BCP‐ALL and T‐ALL was observed. Among these, ten peptides were more highly phosphorylated in BCP‐ALL while 17 peptides showed increased phosphorylation in T‐ALL. Furthermore we selected one lead of the list of commonly activated peptides (HGFR_Y1235) in order to test its efficacy as a potential target and provide proof of principle for this approach. In conclusion kinome profiling is an elegant approach to study active signaling and identify interesting potential druggable targets.